Two-Step Pyrolysis of Spirogyra for Fuels Using Cement Catalytic - Hussain, Z. (Springer Science and Business Media B.V., 2016)
Two-step catalytic pyrolysis of spirogyra, a filamentous alga commonly found in freshwater ditches and ponds, was investigated in a batch pyrolyser under static conditions. The effects of temperature, quantity of catalyst and retention time on properties of the pyrolysis products and yields of the oil, gases and solid residue were investigated. The liquid product obtained by catalytic pyrolysis of the powdered spirogyra was separated into three major fractions by distillation; i.e. a small quantity of flammable liquid, water and a brownish paste-like organic fraction. The paste was converted into a highly flammable gas and oil on catalytic pyrolysis, using cement as catalyst. This oil was analyzed and separated using GC-FID and GCâMS. It was found that the two-step catalytic pyrolysis of spirogyra has potential due to its yield, which had good liquid product density and low oxygen content. Â© 2016, Springer Science+Business Media Dordrecht.